The Urgency of Integration of Local Wisdom Related to Environmental Conservation in the Bangka Belitung Islands - Hasmonel; Derita Prapti Rahayu; Faisal (Faculty of Law, Mulawarman University, 2021)
Local wisdom becomes the full authority of the Regency/City Government as clearly stated in the Table of Division of Authority for the Sub-Division of Local Wisdom Based on Law no. 23 of 2014 concerning Regional Government. Therefore, it is very necessary to know the urgency of the integration of local wisdom related to environmental conservation in the Bangka Belitung Islands. This study uses a socio-legal approach, namely the object of research remains in the form of law, namely laws and regulations related to local wisdom and the environment with the use of methods and theories of social sciences to assist researchers in conducting analysis. Local Wisdom is very important to be integrated in regional policies related to environmental conservation because there is a reciprocal relationship between humans and nature, where people who pay attention to local wisdom related to the environment always place the balance of nature in environmental management and must be accepted or approved, which means that the regulation gets recognition. legitimacy) from the community because it comes from local wisdom that lives in the community.